1986
DOI: 10.3354/meps028291
|View full text |Cite
|
Sign up to set email alerts
|

Chroococcoid cyanobacteria: a significant component in the food web dynamics of the open ocean

Abstract: New techniques used during a recent study in the oligotrophic North Pacific Ocean demonstrated that coccoid cyanobacteria were the most abundant photoautotrophs. Despite their small size, they accounted for 64 % of the total photosynthesis, with specific growth rates of 1.6 d-'. Grazing experiments indicated that a diverse assemblage of micrograzers is able to consume and effectively metabolize chroococcoid cyanobacteria. In the open ocean, a significant trophic interaction occurs between cyanobacteria and mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
53
1
3

Year Published

1987
1987
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(59 citation statements)
references
References 23 publications
2
53
1
3
Order By: Relevance
“…A case for this omission could be defended if small phytoplankton were not quantitatively important, thus making the increased effort an unnecessary cost. However, a growing body of data indicates the importance of pica-and nano-size plankton in a number of major ecosystems throughout the world, including small lakes (Pick 1991), rivers (Edwards et al 1990), large lakes Chang and Petersen 1995), estuaries (Malone et al 1991;hiarte and Purdie 1994), and the open ocean (Iturriaga and Mitchell 1986;Chisholm et al 1988). Aside from the common methodological constraints that we all face, it is our hope here to bridge the conceptual constraints that are often less tangible.…”
Section: Discussionmentioning
confidence: 99%
“…A case for this omission could be defended if small phytoplankton were not quantitatively important, thus making the increased effort an unnecessary cost. However, a growing body of data indicates the importance of pica-and nano-size plankton in a number of major ecosystems throughout the world, including small lakes (Pick 1991), rivers (Edwards et al 1990), large lakes Chang and Petersen 1995), estuaries (Malone et al 1991;hiarte and Purdie 1994), and the open ocean (Iturriaga and Mitchell 1986;Chisholm et al 1988). Aside from the common methodological constraints that we all face, it is our hope here to bridge the conceptual constraints that are often less tangible.…”
Section: Discussionmentioning
confidence: 99%
“…Picophytoplankton (photosynthetic picoplankton) have been shown to make a significant contribution to planktonic biomass (e.g., Li et al 1983;Takahashi et al 1985;Gradinger et al 1992) and productivity Iturriaga & Mitchell 1986) in oligotrophic regions of the ocean. Earlier observations suggested that these smallcelled phototrophs were primarily a feature of offshore oligotrophic environments (Stockner & Antia 1986) but more recent work indicates that they can also be a major component of coastal and estuarine waters, including nutrient rich environments (e.g., Hall & Vincent 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Synechococcus and Prochlorococcus are estimated to absorb approximately 1×10 10 Tg carbon from the atmosphere each year, which is equivalent to two-thirds of the total carbon fixation that occurs in the oceans [36]. Chroococcidiopsis, a unicellular, non-heterocyst-differentiation genus, is a wide-spread cosmopolitan unicellular cyanobacteria found in many extreme environment, such as the airspaces of porous rocks, Antarctic valleys and hot deserts [37].…”
Section: Discussionmentioning
confidence: 99%